The Motor System: The Whole and its Parts - E. Otten (Neural Plasticity)
Our knowledge of components of the human motor system has been growing steadily, but our understanding of its integration into a system is lagging behind. It is suggested that a combination of measurements of forces and movements of the motor system in a functionally meaningful environment in conjunction with computer simulations of the motor system may help us in understanding motor system properties. Neurotrauma can be seen as a natural deviation, with recovery as a slow path to yet another deviant state of the motor system. In that form they may be useful in explaining the close interaction between form and function of the human motor system.